Pendampingan Hukum Penyelamatan Asset Warga Desa Terban yang Menjadi Jaminan Kredit pada Koperasi Artha Jaya Kudus - Wiwit Ariyani; Yusuf Istanto (Muria Jurnal Layanan Masyarakat, 2021)
The objectives of this service are: (i) Reviewing the settlement of civil cases both through the court (litigation) and outside the court (non litigation / out of settlement). The second objective (ii) examines a model for settling civil cases outside the court through non-court mediation. The novelty of this service will seek a settlement model through out-of-court mediation. Koperasi Artha Jaya Jekulo Kudus holding a collateral object in the form of a certificate of ownership of land registered in the name of Warsini is a violation of the law stipulated in Article 372 of the Criminal Code in the form of extortion and threats. In addition to detaining the object of collateral for the Artha Jaya Jekulo Kudus Cooperative, collateralizing the BPR BKK Jati Kudus without the knowledge of the owner is a violation of the law regulated in clause 263 paragraph (1) in the form of forging documents, which faked Warsini's signature on the Credit Agreement between Artha Cooperatives. Jaya Jekulo Kudus with BPR BKK Jati Kudus. The output of this service is the return of certificates belonging to residents of Dukuh Krangit, Terban Village who are still detained at the Artha Jaya Cooperative and third parties, a model for resolving civil cases outside the court through non-court mediation and publication in journals. Keywords: Credit, Legal Assistance, Case Settlement